TEACHER PRAISES AND STUDENTS’ ENGAGEMENT IN EFL CLASSROOM (A case study of seventh grade students at one of junior high school in Bandung) - Farah Hanifah Firdaus (Journal of English and Education, 2015)
The study analyzed the use of praise and its influence toward students’ engagement. Qualitative approach was employed in this study. The obtained data were analyzed by using the theory of effective praise by Conolly et al (1995) and also the theory of characteristics of students’ engagement by Jones (2009). The data of this study were obtained from classroom observation. The result of this study showed that the way teacher gives praise to the students is in line with the theory of effective praise. The observed teacher in this study gave praise to the students in four steps: description of appropriate behavior, rationale, request acknowledgment, and positive consequence. In addition, the result of the study also showed students’ positive engagement after being praised by the teacher. There were five characteristics of students’ engagement that appeared during classroom observation: positive body language, consistent focus, verbal participation, students’ confidence, and fun and excitement. In conclusion, the use of praise would influence students’ positive engagement if it was given properly.